On the behaviour of voters and politicians: municipal elections and the economy - Carvalho, Bruno Pessoa (2019)
This thesis investigates the behaviour of politicians and voters in local elections. The first paper studies the effects of campaigning when public funding covers a sizeable share of spending. It develops a probabilistic voting model and a causal, instrumental variable, empirical analysis using a novel database of political campaigns from the Portuguese Constitutional Court. The second paper is a field-experiment that evaluates the impact of the information conveyed by the media to the voters on their political perceptions and voting behaviour. In the last, I use the fact that mayors increase spending in election years to estimate the local economic impacts of increased expenditure.